TAX POLICY DEVELOPMENTS AND REFORM IN AUSTRALIA: MUCH UNFINISHED BUSINESS - Fernandez, Prafula; Pope, Jeff (The journal of contemporary issues in business and government, 2009)
Following an earlier paper written by the authors relating to Australian tax reform in the British Tax Review in 2001, this paper reviews the Australian tax reform and policy over the period 2000-01 to 2007-08 and discusses the successful implementation of Australia’s Goods and Services Tax and associated reforms under A New Tax System as well as the overall characteristics of Australia’s tax system. The paper also assesses reform in international tax, the significant superannuation and retirement policy changes from July 2007 and the review of income tax self assessment. Tax policy reform for small business and its failure to actually simplify as intended (at least until recently perhaps) is also examined, as is the forthcoming regulatory reform affecting tax agents and future reforms in two important policy areas, namely the efficiency of Australia’s tax-transfer system and its proposed carbon pollution reduction scheme (both currently under government review). Recent UK tax policy is discussed from an overseas perspective and compared to Australian reform. Three overarching problems for Australian taxation policy are identified in the conclusions.